The Mediating Role of Learning Motivation in the Relationship between Perception of Lecturer Competence and College Student Learning Achievement in English Learning Subject (Jurnal Sosial Humaniora dan Pendidikan, 2025)
This study aims to identify the influence of lecturer competence on student learning achievement mediated by learning motivation at the University of Computer Science and Technology. This study uses a quantitative approach. Data were collected using a questionnaire with measurements using a Likert scale of 1-5. The population in this study were all students of the University of Computer Science and Technology who took English courses. The sample consisted of 40 respondents selected using convenience sampling techniques. The data analysis technique used PLS-SEM with testing using the SmartPLS application version 4.1.1.2. The results of this study analysis revealed the results of the influence of lecturer competence and learning motivation have a significant effect on student learning achievement. The lecturer competence variable has a significant effect on student learning achievement. The lecturer competence variable also has a positive and significant effect on student learning motivation. Learning motivation is proven to be able to mediate the influence of lecturer competence on student learning achievement.